Depletion of the m1A writer TRMT6/TRMT61A reduces proliferation and resistance against cellular stress in bladder cancer - Monshaugen, Ida; Luna, Luisa; Rhodes, Jayden; Kristiansen, Felicia Iselin Svensson; Lång, Anna; Bøe, Stig Ove; Dutta, Anindya; Su, Zhangli; Klungland, Arne; Ougland, Rune (Frontiers in Oncology, 2024)
Background: Bladder cancer (BLCA) is a common and deadly disease that results in a reduced quality of life for the patients and a significant economic burden on society. A better understanding of tumorigenesis is needed to improve clinical outcomes. Recent evidence places the RNA modification m1A and its regulatory proteins TRMT6/TRMT61A and ALKBH3 in BLCA pathogenesis.Methods: TRMT6/TRMT61A, ALKBH1, and ALKBH3 expression was examined in human BLCA cell lines and a normal urinary tract epithelium cell line through qRT-PCR and western blot analysis.Prestoblue Cell Viability Reagent, wound-healing assay, and live-cell imaging-based cell displacement analysis, were conducted to assess proliferation, migration, and displacement of this BLCA cell line panel. Cell survival was assessed after inducing cellular stress and activating the unfolded protein response (UPR) with tunicamycin. Moreover, siRNA-mediated gene silencing in two BLCA cell lines (5637 and HT1197) was conducted to investigate the biological roles of TRMT6/TRMT61A.Results: Heterogeneous morphology, proliferation, displacement, tunicamycin sensitivity, and expression levels of m1A regulators were observed among the panel of cell lines examined. In general, TRMT61A expression was increased in BLCA cell lines when compared to SV-HUC-1. Depletion of TRMT6/TRMT61A reduced proliferation capacity in both 5637 and HT1197 cell lines. The average cell displacement of 5637 was also reduced upon TRMT6/TRMT61A depletion. Interestingly, TRMT6/TRMT61A depletion decreased mRNA expression of targets associated with the ATF6branch of the UPR in 5637 but not in HT1197. Moreover, cell survival after induction of cellular stress was compromised after TRMT6/TRMT61A knockdown in 5637 but not in HT1197 cells.The findings suggest that TRMT6/TRMT61A plays an oncogenic role in BLCA and is involved in desensitizing BLCA cells against cellular stress. Further investigation into the regulation of TRMT6/TRMT61A expression and its impact on cellular stress tolerance may provide insights for future BLCA treatment.